Pengaruh Brand Experience Dan Brand Trust Terhadap Loyalitas Konsumen Pada Penggunaan Produk Scarlett Whitening Di Kabupaten Kolaka - Sitti Hasnani; Andry Stepahnie Titing; Hendrik (CV. ITTC INDONESIA, 2022)
The purpose of this study was to determine the effect of brand experience and brand trust on consumer loyalty in using Scarlett Whitening products in kolaka district. This research is a quantitative research model using a questionnaire in this study were all consumers who use scarlett whitening products with a total sample of 65 respondents using a purposive sampling technique. Data collection techniques are primary data and secondary data. The data obtained were analyzed using PLS analysis techniques through the SmartPLS Software. The results of this study show primary and secondary data. The data obtained were analyzed using PLS analysis techniques through the SmartPLS software. The results of this study indicate that brand experience has a positive and significant effect on consumer loyalty. This is evidenced by the t-count or t-statistic, which is 3.967, wich is higher than the t-table value, which is > 1.669. Brand trust also has a positive and significant effect on consumer loyalty because the t-count or t-statistic value of 3.046 is higher than the t-table value > 1.669. So brand experience and brand trust have a positive and significant effect on concumer loyalty by 74.1% while 25,9% is influenced by other factors not examined in this study .